Parameter influences of FTO/ZnO/Cu₂O photodetectors fabricated by electrodeposition and spray pyrolysis techniques - Muthiah N. Najah; Frida A. Rahmania; Integralita Cahyanti; Maulida Hesnaty; Siti Hajar Alias; Djoko Hartanto; Wahyu Prasetyo Utomo; Retno Sari; Hadi Nur (South African Journal of Chemical Engineering)
This study investigates fabrication of transparent conductive glass using fluorine-doped tin oxide (FTO) as a more affordable alternative to indium tin oxide (ITO) in photovoltaic applications. To enhance conductivity, a ZnO layer was deposited on FTO, followed by a Cu2O layer via electrodeposition. The synthesis parameters are varied to determine their effect on the reaction and to identify the optimal conditions. The characteristic of FTO/ZnO/Cu2O studied using XRD, SEM annexed with EDX, IV testing and visible light absorption spectroscopy to disclose its optoelectronic applications. The FTO layers were produced via spray pyrolysis, with optimal deposition achieved at 400 °C and efficiency value 0.0149 %, resulting in a dense, transparent structure. Meanwhile the efficiency of samples at temperatures of 350°C, 450°C, and 500°C are 0.0032 %, 0.0042 %, and 0.0037 %. From the efficiency results, the optimal thickness of the Cu2O layer was obtained at a duration of 30 min, which was 0.0380 %, while the other durations of 1 hour, 2 h, and 3 h were 0.0149 %, 0.0076 %, and 0.0056 %. The best efficiency was obtained at an optimum pH of 10 with a value of 0.0038 %, promoting crystal growth along the (111) plane. While at pH variations of 8, 9, 11, and 12, the efficiency values were 0.0016 %, 0.0083 %, 0.0083 %, and 0.0073 %, respectively. I-V testing of FTO/ZnO:Mg/ Cu2O with varying electrodeposition voltage show that the efficiency of samples at voltage 5 V, 10 V, 15 V, 20 V, and 0.0128, 0.0093, 0.0036, 0.0053 and 0.0383 %. The optimum conditions for fabricated the samples was achieved with a 30-minute electrodeposition duration at 25 V and pH 10, as confirmed through I-V testing. The study highlights the influence of pyrolysis temperature, electrodeposition time, and pH on the optical and electrical properties of the glass, with optimized conditions yielding improved photoresponse performance.